Women in the Zambian civil service: a case of equal opportunities? - Turner Thomas; O'Connor Pat
There is a paucity of empirical microlevel studies of women in the formal sector in developing countries. This article attempts to redress this deficit and focuses on the position of women in the Zambian civil service using information from a sample of personnel records. Although women are disproportionately represented in the civil service compared with other areas of the formal economy, the current positions of males and females are significantly different. However, the results of the survey are not easily encompassed in the prevailing theoretical frameworks and, rather surprisingly, it appears that it is age rather than gender that is the crucial explanatory variable. Finally, a number of possible explan
Keywords: Civil Service -- Zambia; Women in the Civil Service -- Zambia